Evaluasi Penerapan Computer Based Test (CBT) sebagai Upaya Perbaikan Sistem pada Ujian Nasional untuk Sekolah Terpencil di Sumatera Selatan: - - Eka Hartati; Mardiana Mardiana (Universitas Bumigora, 2018)
Academic year there were 2014/2015 the latest national test that policy can be implemented in two ways, the first national examination was carried out with the mechanics in writing or Paper Based Test (PBT), and the second national examination is carried out by the mechanism uses a computer or Computer Based so-called Test (CBT). Computer Based Test (CBT) for its implementation, where all test process was done through computers, ranging from the creation of matter, the setting class, setting the user can take the exam, the teacher was teaching, setting up the test process, utilizing web engineering technology, as well as its spring system online. Academic year 2016/2017 in South Sumatra by as much as 261 high schools both public and private have been implementing a national exam in the form of Computer-Based Test (Kemendikbud 2017). This study sampled in ten high schools located in remote villages. In understanding and knowledge about the use of technology-based desktop application specifically at schools that are in remote villages is insufficient, in karenakan least amount of computers and teachers who are in school. The purpose of this research was to measure the application of Computer Based Test using variable effectiveness and efficiency on the basis of ISO 9126. In this study researchers use quantitative research methods with the application of the model of ISO 9126, which consists of a variable effectiveness and efficiency. This research use the measuring instrument in the form of a questionnaire consisting of 297 respondents out of ten high school, where the measurement scale that is used in the form of data analysis and likert scale done testing the validity of, reabilitas and regression Double